Association of alkaptonuria and low dose nitisinone therapy with cataract formation in a large cohort of patients. Issue 4 (9th April 2022) - Ahmad, Mohammad S. Z.; Ahmed, Mahmoud; Khedr, Milad; Borgia, Alfredo; Madden, Andrea; Ranganath, Lakshminarayan R.; Kaye, Stephen
Abstract: Homogentisic acid (HGA) lowering, disease modifying off‐label nitisinone therapy has been used in the United Kingdom National Alkaptonuria Centre (NAC) since 2012. This study evaluated the serendipitous observation of cataract in a large cohort of patients with the very rare disease alkaptonuria (AKU), over a 5‐year period. Patients with AKU who attended the NAC since 2012. Standard physical examination and ocular assessment, including photographs of the crystalline lens were taken before commencement of nitisinone 2 mg daily and annually over 5 years. Photographs were randomised and graded by two independent observers using the WHO cataract classification. AKU patients who did not receive nitisinone were included as a control group. HGA was measured on acidified 24 h urine (u‐HGA24 ) and HGA and tyrosine in fasting acidified serum samples (sHGA, sTYR) at each visit. Patients without suitable lens images were excluded. Cataract (mean grade 1) was noted at baseline in 47 out of 62 (76%) with a mean (SD) age of 44 (14) years. In nitisinone‐treated patients, there were significant increases in the mean grade of nuclear (0.18, p < 0.01) and cortical (0.38, p < 0.01) lens opacities over the mean duration of 4.93 years of the study. Worsening of the nuclear cataract and cortical lens opacities by at least 1 grade was noted in 14 out of 46 (30%) and 11 out of 46 (24%) patients, respectively. There is an increased prevalence and progression of cataract in AKU and a possible association of nitisinone with cataract progression.